2010
DOI: 10.1371/journal.pone.0010465
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Zebrafish Interactome Reveals Transcriptional Mechanisms of Dioxin Toxicity

Abstract: BackgroundIn order to generate hypotheses regarding the mechanisms by which 2,3,7,8-tetrachlorodibenzo-p-dioxin (dioxin) causes toxicity, we analyzed global gene expression changes in developing zebrafish embryos exposed to this potent toxicant in the context of a dynamic gene network. For this purpose, we also computationally inferred a zebrafish (Danio rerio) interactome based on orthologs and interaction data from other eukaryotes.Methodology/Principal FindingsUsing novel computational tools to analyze this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 95 publications
3
52
0
Order By: Relevance
“…The interactome backbone contains 5,760 nodes (protein-protein and protein-DNA interactions) and 99,573 relationships between these proteins (interactions). The designation of protein properties was drawn from Alexeyenko et al 2010 18 NCBI gene name attributes were used to unify the protein list and were imported through the Biomart plugin. The network for the zebrafish challenges was built from within the Danio_rerio_CS interactome.…”
Section: Microarray Analysesmentioning
confidence: 99%
“…The interactome backbone contains 5,760 nodes (protein-protein and protein-DNA interactions) and 99,573 relationships between these proteins (interactions). The designation of protein properties was drawn from Alexeyenko et al 2010 18 NCBI gene name attributes were used to unify the protein list and were imported through the Biomart plugin. The network for the zebrafish challenges was built from within the Danio_rerio_CS interactome.…”
Section: Microarray Analysesmentioning
confidence: 99%
“…Although high-throughput methods have been used widely for years, they have primarily been used to screen a few responding genes rather than for network analysis at the genome level. Taking the three toxicants we investigated as examples, recent studies on network analysis of environmental pollutants have primarily focused on classical genes and pathways [45][46][47][48][49][50][51]. Thus, a suitable model and a corresponding method for network analysis at the genome level are required.…”
Section: Network Analysis Of Tcdd In T Thermophilamentioning
confidence: 99%
“…In zebrafish for example, while nrf2a has been shown to be up-regulated by TCDD (Hahn, et al, 2014), zebrafish embryos sampled immediately after a 6 h exposure to TCDD showed no evidence of altered expression of other genes typically found in the oxidative stress response at 4 dpf, and there was an increase in gstp1 expression only after 48 h of a TCDD exposure that began at 24 hours post fertilization (hpf) (Hahn, et al, 2014). An oxidative stress response was not observed in response to TCDD at least two other studies (Alexeyenko et al ., 2010; Wang et al ., 2013). This may be due to many factors including differences in timing, dose, developmental stage, species sensitivity to Ahr ligand binding, or exposure duration, or it is possible that ROS generation may not always be sufficient to alter redox signaling or activate an oxidative stress response.…”
Section: Introductionmentioning
confidence: 78%